On the molecular basis of transition mutations: frequencies of forming 2-aminopurine.cytosine and adenine.cytosine base mispairs in vitro. - Watanabe, S M (1981)
We address the question of whether substituting 2-aminopurine (APur) in place of adenine (Ade) in DNA can increase the frequency of base mispairing with cytosine. Using DNA polymerase alpha to measure the rates of inserting deoxycytidine and thymidine nucleotides in direct competition with each other for APur or Ade sites on synthetic copolymer DNA templates, we observe that the ratio of dCMP to dTMP insertion is increased by a factor of at least 230 when APur replaces Ade on a poly(dA) template and by a factor of 35 when APur replaces Ade on a poly(dC,dA) template. These data support the idea that APur.C base mispairs are directly involved in APur induction of A.T leads to G.C transition mutations. The observed misinsertion frequency of cytosine substituting for thymine opposite template APur sites is about 5%. This value is in excellent agreement with earlier predictions and measurements for APur.C heteroduplex-heterozygote frequencies in T4 bacteriophage in vivo.